A posztszocialista átalakulási válság a mezőgazdaságban és a falusi társadalomban (Szociológiai Szemle, 2024)
After a decade of recession and with the fall of state socialism one hoped a fast regeneration of agriculture.The last five years were not moving Hungarian agriculture out of long period of slow growth. They were instead pushing it into a painful crisis of transformation, which devastated the whole economy, but its impact on agriculture was particularly damaging. While private property and market gained more importance this is not quite a „Capitalist Market Economy" based on complex new property rights.